Vertical Flow Constructed Wetland Design for Domestic Wastewater Treatment for Communal Scale in DKI Jakarta Environmental Service Dormitory - Putra, Giovanni Ruly; Ridhosari, Betanti; Sofiyah, Evi Siti; Zahra, Nurulbaiti Listyendah; Sarwono, Ariyanti; Suryawan, I Wayan Koko (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2023)
To better manage Jakarta's domestic wastewater, the DKI Jakarta Provincial Government commissioned the construction of Domestic Wastewater Treatment Plants (WWTP) in multiple locations across the city. After the results of the measurements have been determined, engineering work needs to order to address the numerous parameters more than excesses of the quality in addition, there. This study intends to develop a vertical flow CW design as an additional treatment for the DKI Jakarta Environmental Service Dormitory Communal Domestic WWTP as a recommendation for improvement so that the quality of treated water can meet domestic wastewater quality standards. This study aims to ensure that the quality of treated water can meet domestic wastewater quality standards. This redesign makes use of a variety of data sources, including primary data as well as secondary data. The necessary information is the quantity of constable water consumption and the quality of the domestic wastewater produced within the environment of the DKI Jakarta DLH Dormitory. Through a network of pipelines, wastewater from activities such as bathing and using the latrines is transported directly to the WWTP. During this time, water from activities such as washing and runoff caused by rain will enter various drainage channels to the receiving water body, the Ciliwung River. The length of the CW at WWTP 1 is 6.718 meters, and its width is 3.35 meters. Following more in-depth processing of the available data, it was discovered that the existing outlet wastewater had a low C/N ratio. When creating wetlands in the field using artificial CW, the discharge that flows into the wetland and the release that flows out of the wetland is not the same. The amount can either be decreased or increased according to the current circumstances. This needs to be considered for the presence of water in the swamp system to be managed. After being processed with VFCW, it was discovered that the total BOD value of the effluent produced was less than 30 mg/L. This suggests that the processing of VFCW can conform to the requirements of PermenLHK No. 68/2016, which is concerned with the Quality Standards for Domestic Wastewater. The ammonium-nitrogen value by comparing the molar mass value to NH3. As a result, WWTP locations 1, 2, and 3 have all achieved the required quality. The NH4 value, on the other hand, has not been able to meet the quality standard of PermenLHK No. 68/2016 concerning Domestic Wastewater Quality Standards. This is because the ammonia concentration from Domestic Communal WWTP 4 is so high. As a solution to this problem, WWTP 4 will be upgraded from four plants per square meter (ppm) to five plants per sq m (ppm), hoping to improve the rate at which plants absorb nutrients. The removal of ammonia using VFCW can range anywhere from 34 - 95 percent. Keywords: Domestic Wastewater, Planning, Constructed Wetland, WWTP